Wages and human capital in exporting firms in Morocco - Christophe Muller; Christophe Nordman (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2006)
We study the relationship of wages, human capital accumulation and work organisation in Morocco using matched worker-firm data for Metallurgical-electrical and Textile-clothing firms. While wages are found to rise with all human capital characteristics, returns to education and experience are much higher for the upper wages. Participation in on-the-job training is constrained by: a relevant industrial location; a minimal educational background; and an appropriate family situation. Moreover, work organisation and on-thejob training are dependent on the education process. Finally, we find that strong interactions of human capital accumulation with involvement in chain gangs, team work and supervision.
Keywords: 330; Africa; Morocco; Wages; On-the-job training; Human capital; Workplace organisation; Matched worker-firm data